2016
DOI: 10.1016/j.biortech.2016.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Reuse of microalgae grown in full-scale wastewater treatment ponds: Thermochemical pretreatment and biogas production

Abstract: This study assessed thermochemical pretreatment of microalgae harvested from a full-scale wastewater treatment pond prior to its anaerobic digestion using acid and alkaline chemical doses combined with thermal pretreatment at 80°C. Results indicated that alkaline and thermal pretreatment contributed mostly to glycoprotein and pectin solubilisation; whilst acid pretreatment solubilised mostly hemicellulose, with lower effectiveness for proteins. Regarding the anaerobic biodegradability, biochemical methane pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 45 publications
(18 citation statements)
references
References 18 publications
0
16
0
2
Order By: Relevance
“…Although C pretreatment reported a slightly higher volatile solids release than D, the biogas production was remarkably lower and very similar to the untreated biomass (C1: 173 mLCH 4 /g VS; 42% biodegradability and NP 1.08) and also contained a considerable lag phase. Passos et al, (2016a) reported increases on methane production of 82% with respect to the untreated biomass for alkaline pretreatment at low NaOH concentrations (0.5%, 80ºC, 2 hours), but the methane production from the untreated biomass was very low in this study (78 mL CH 4 /g VS).…”
Section: Test 1: Bmp Of Untreated Raw Materials and Of Pretreated Whomentioning
confidence: 79%
See 4 more Smart Citations
“…Although C pretreatment reported a slightly higher volatile solids release than D, the biogas production was remarkably lower and very similar to the untreated biomass (C1: 173 mLCH 4 /g VS; 42% biodegradability and NP 1.08) and also contained a considerable lag phase. Passos et al, (2016a) reported increases on methane production of 82% with respect to the untreated biomass for alkaline pretreatment at low NaOH concentrations (0.5%, 80ºC, 2 hours), but the methane production from the untreated biomass was very low in this study (78 mL CH 4 /g VS).…”
Section: Test 1: Bmp Of Untreated Raw Materials and Of Pretreated Whomentioning
confidence: 79%
“…They reported an increase in methane production up to 82% and 86% compared to the untreated biomass (78 mL CH4/g VS) for alkaline and acid pretreatments, respectively. Nevertheless, Passos et al, (2016a) also observed an inhibitory effect under severe pretreatment conditions. Most of the reported degradation compounds generated by pretreatments in algae or other types of biomasses were soluble and released to the liquid phase Bolado, 2014, Bolado-Rodríguez et al, 2016).…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations